Good Corporate Governance As A Corporate Strategy During The Covid-19 Pandemic in Islamic Financial Institutions - Happy Sista Devy; Husni Awali; Rita Hadiyati; Aurell Achza Rayne Effendi (Mutanaqishah: Journal of Islamic Banking, 2021)
The purpose of the research is to see the implementation of Good Corporate Governance as a corporate strategy during the COVID-19 pandemic. The type of research conducted is field research with qualitative methods. Data collection techniques used interviews and observations, with data reduction analysis and data triangulation. The results showed that PNM Mekaar sharia Brebes district and BMT Bina Ummat Sejahtera Bumiayu Brebes district applies the principles of Good Corporate Governance (GCG) well in the form of the principles of Transparency, Accountability, Responsibility, Independence, and Fairness. Where the implementation of Good Corporate Governance (GCG) as a company strategy during the Covid-19 pandemic has a positive impact on the company by increasing customers and members who need financing.